PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DENGAN KOMPENSASI SEBAGAI VARIABEL MODERATING PADA PT. PLN UNIT PELAKSANA PELAYANAN PELANGGAN (UP3) SITUBONDO - Fatah, Ahmad Zainul; Wahyuni, Ika; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2024)
PLN Customer Service Implementation Unit (UP3) Situbondo serves customers directly. Thus, the human resources involved can develop better interpersonal and communication skills, and increase sensitivity to customer needs and expectations. This study aims to analyze the influence of transformational leadership, work motivation, and compensation on employee performance at PT PLN Customer Service Implementation Unit (UP3) Situbondo. The population in this study were employees of PT. PLN Customer Service Implementation Unit (UP3) Situbondo. This study was conducted using a quantitative approach and the sampling technique was determined by quota sampling. Data analysis and hypothesis testing in this study used Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results of the hypothesis test using the Smart PLS 3.0 application showed that transformational leadership had a significant effect on performance, and work motivation had a significant effect on performance. The results of the hypothesis test using compensation as a moderating variable showed that the transformational leadership variable had a positive effect but not significant on performance, and work motivation variable moderated by compensation showed a positive effect on performance but not significant.